THE PROBLEM OF OPENNESS OF THE SYSTEM OF SOCIAL MORALITY - V. V. Nadurak (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of this paper is to investigate the specificity of the openness of the system of social morality to influence of the various phenomena of natural and social being. To achieve this goal it is necessary to identify the control factors of the system of social morality and describe characteristics of their interaction with the system. Methodology. The research is based on the use of synergetic methodology, according to which social morality is treated as an open complex self-organizing system. The openness and non-linearity are the main methodological principles of synergetics, which were used in the study. Scientific novelty of the research lies in the fact, that the idea of openness of the system of social morality to influence of the various phenomena of natural and social being and, above all, those that can be called «control factors» has been comprehensively investigated for the first time. It is noted nonlinear connection between system of social morality and its control parameters, the existence of circular causality between them, the difference in the intensity of the influence of different control factors on morality. Conclusions. Openness of the system of social morality provides, that external factors have an impact on it. Among them there are factors which impact is most relevant. We call them the control factors of the system of social morality. They can be divided into two main groups: the first are those, that have a social origin, and the second – biological. Macro level of morality (moral consciousness) is a new quality in comparison with the control factors. It is not their linear extension, because though it is formed by their influence, but the immediate cause of its appearance is self-organization mechanisms. Control factors are differ by the intensity of their impact on the system of social morality. Among them are those, which can be considered as fundamental, because structures, which are formed under their influence, are the basis of morality. The influence of others is usually lower, although at certain periods of system development it may increase or decrease. Interaction between the system of social morality and its controlling factors is characterized by circular causality: controlling factors affect morality and, in turn, they are subject to its influence.